Pengaruh Kejelasan Sasaran Anggaran dan Sistem Pelaporan terhadap Akuntabilitas Kinerja dengan Pengendalian Internal sebagai Variabel Intervening pada SKPD Pemerintah Kabupaten Kotabaru - Sanusi Sanusi; Padlah Riyadi (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2023)
This study aims to examine the effect of the clarity of budget objectives and reporting systems on the performance accountability of government agencies. This study is also to test whether the internal control system mediates the effect of the clarity of government budget objectives and reporting systems. This type of research is associative causality. This research was conducted using a survey method by distributing questionnaires to the compilers of performance accountability reports of government agencies in Kotabaru. The population of this study was all SKPD in the Kotabaru Regency Government, totaling 30 SKPD consisting of 82 sample respondents. The data analysis method used is descriptive statistical analysis and Partial Least Square (SEM-PLS) analysis. The analysis is assisted by the Smart PLS 3.0 program. The results of this study indicate that the clarity of budget targets and internal control affect the performance accountability of government agencies while the reporting system has no effect on performance accountability. Clarity of budget targets, and reporting systems affect internal control. Internal control as an interverning variable can affect the clarity of budget objectives and the accountability reporting system for the performance of the Kotabaru local government agencies.